Dimerization of Human XPA and Formation of XPA(2)-RPA Protein Complex - Yang, Zheng-guan (2002)
XPA plays an important role in the DNA damage recognition during human nucleotide excision repair. Here we report that the XPA is a homodimer either in the free state or as a complex with human RPA in solution under normal conditions. The human XPA protein purified from baculovirus-infected sf21 insect cells has a molecular mass of 36 317 Da, as determined by mass spectroscopy. However, the apparent molecular mass of XPA determined by the native gel filtration chromatography was about 71 kDa, suggesting that XPA is a dimer. This observation was supported by a native PFO-PAGE and fluorescence spectroscopy analysis. XPA formed a dimer (XPA(2)) in a broad range of XPA and NaCl concentrations, and the dimerization was not due to the disulfide bond formation. Furthermore, a titration analysis of the binding of XPA to the human RPA indicated that it was the XPA(2) that formed the complex with RPA. Finally, the difference between the mass spectrometric and the calculated masses of XPA implies that the protein contains posttranslational modifications. Taken together, our data suggest that the dimerization of XPA may play an important role in the DNA damage recognition of nucleotide excision repair.